2011
DOI: 10.1007/s00421-011-2065-2
|View full text |Cite
|
Sign up to set email alerts
|

Beverage carbohydrate concentration influences the intermittent endurance capacity of adolescent team games players during prolonged intermittent running

Abstract: This study investigated the influence of consuming a 2, 6, and 10% carbohydrate-electrolyte (CHO-E) solution on the intermittent endurance capacity and sprint performance of adolescent team games players. Seven participants (five males and two females; mean age 13.3 ± 0.5 years, height 1.71 ± 0.05 m, body mass (BM) 62.0 ± 6.3 kg) performed three trials separated by 3-7 days. In each trial, they completed four 15-min periods of part A of the Loughborough Intermittent Shuttle Test (LIST) followed by an intermitt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 35 publications
0
14
0
Order By: Relevance
“…Similarly, a recent study demonstrated greater endurance capacity when ingesting moderate-CHO solutions as compared to low-and high-CHO solutions (26).…”
Section: Discussionmentioning
confidence: 96%
“…Similarly, a recent study demonstrated greater endurance capacity when ingesting moderate-CHO solutions as compared to low-and high-CHO solutions (26).…”
Section: Discussionmentioning
confidence: 96%
“…It is common practice for team sport athletes to consume carbohydrate (CHO) to improve intermittent exercise capacity [5,6] and endurance performance [7,8], which is thought to occur via central nervous system (CNS) activation and other potential mechanisms such as higher rates of CHO oxidation [9,10]. Another ergogenic aid that has routinely been used by athletes is caffeine (CAF) [11].…”
Section: Introductionmentioning
confidence: 99%
“…In a follow up study, Phillips et al [43] investigated the influence of different carbohydrate concentrations (2%, 6%, and 10% maltodextrin solutions) on the same variables as their initial study. The identical exercise protocol and measurements, and the fact that the participants (n = 7, 5 males and 2 females) all took part in the first study, strengthens between-study comparisons.…”
Section: Please Insert Table I Herementioning
confidence: 99%
“…[44] The age range and maturation status of participants was similar to the previous investigations. Body-mass relative gel ingestion rate was equal to that of Phillips et al [42] and Phillips et al [43] (6% trial), enabling a direct comparison between the efficacy of an isoenergetic carbohydrate solution and gel. [44] The carbohydrate gel significantly increased mean time to exhaustion by 21.1%, with no treatment effect on sprint time or physiological responses.…”
Section: Please Insert Table I Herementioning
confidence: 99%
See 1 more Smart Citation